Hybrid control of grid-feeding and fuzzy logic fault detection in solving voltage dynamic problem within the malaysian distribution network - Hoe O.K.; Ramasamy A.K.; Yin L.J.; Verayiah R.; Marsadek M.B.; Abdillah M. (MDPI AG, 2023)
Electric load dispatching; Electric power transmission networks; Electrolysis; Energy storage; Fault detection; Feeding; Fuzzy control; Fuzzy logic; Photovoltaic cells; Power quality; Reactive power; Solar power generation; Stochastic systems; Active power compensation; Additional equipment; Control complexity; Distribution levels; Fault detection schemes; Mode of operations; Reactive power compensation; Stochastic behavior; Electric power system control